2011
DOI: 10.1890/10-0280.1
|View full text |Cite
|
Sign up to set email alerts
|

Managing soil nitrogen to restore annual grass-infested plant communities: effective strategy or incomplete framework?

Abstract: Theoretical and empirical work has established a positive relationship between resource availability and habitat invasibility. For nonnative invasive annual grasses, similar to other invasive species, invader success has been tied most often to increased nitrogen (N) availability. These observations have led to the logical assumption that managing soils for low N availability will facilitate restoration of invasive plant-dominated systems. Although invasive annual grasses pose a serious threat to a number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 85 publications
4
69
0
1
Order By: Relevance
“…The rate remained higher during growth of D. ciliaris aimed at rapid acquisition of nutrients in environments without limitations is a feature associated with annual grasses in general (James et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…The rate remained higher during growth of D. ciliaris aimed at rapid acquisition of nutrients in environments without limitations is a feature associated with annual grasses in general (James et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…A number of investigators have found trends similar to those in our study where nitrogen addition reduced growth of native species and either enhanced or had no effect on non-indigenous, invasive species. In the western United States increases in growth of non-indigenous, annual grasses at the expense of native, perennial grasses is widely attributed to increases in nitrogen (see reviews by James et al 2011 andVasquez 2008). These trends are often found at relatively low levels of nitrogen supplementation; among the studies included in the review conducted by James et al…”
Section: Resultsmentioning
confidence: 99%
“…Increases in soil nitrogen deposition are often positively correlated with non-indigenous and indigenous invasive species fitness, establishment and spread (Abraham et al 2009, Bell and Treshow 2002, Burke and Grime 1996, Hobbs et al 1988, Metcalfe and Fowler 1998, SchererLorenzen et al 2000, Vasquez 2008, Wedin and Tilman 1996, McLendon and Redente 1991, Melgoza and Nowak 1991, Kolb et al 2002, Brooks 2003, Norton et al 2007, Vasquez 2008and references therein, MacKown et al 2009, James et al 2011 and references therein).…”
mentioning
confidence: 99%
“…As plantas daninhas, em geral, apresentam crescimento inicial rápido, com altas taxas de crescimento relativo nos 50 DAS, com objetivo de absorver nutrientes e se desenvolver em ambientes sem limitações, podendo assim se estabilizar no ambiente (RAVINDRA et al, 2008;JAMES et al, 2011;SALEHIAN;ESHAGHI, 2012).…”
Section: Análise De Crescimento De Espécies Daninhas Do Gênero Euphorbiaunclassified